(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
Sharks present strong intraspecific changes in feeding habits, which may vary according to size, geographic location and season. This study analyzed the stomach contents of 52 juvenile scalloped hammerhead sharks (25 females and 27 males) caught by artisanal vessels in the Gulf of Nicoya. Regarding the organisms found in the stomachs, 41.07 % were teleost fish, 30.36 % mollusks and 28.57 % crustaceans. Mollusks presented the highest Relative Importance Index (RII) (43.05 %), followed by teleost fish (41.37 %) and crustaceans (15.58 %). Squids (Loliginidae) were the items with the greatest RII (32.57 %). By means of the Pianka index, a relatively low overlap between sexes was identified, suggesting a spatial sexual segregation and, in consequence, an ecological niche separation between male and female hammerhead sharks.